Early Emergence of Rumination has no Association with Performance on a Non-affective Inhibitory Control Task. - Thomas, Leah R.; Bessette, Katie L.; Westlund Schreiner, Melinda; Dillahunt, Alina K.; Frandsen, Summer B.; Pocius, Stephanie L.; Schubert, Briana Lee; Farstead, Brian W.; Roberts, Henrietta; Watkins, Edward R.; Kerig, Patricia K.; Crowell, Sheila E.; et al. (Child Psychiatry & Human Development, 2024)
Rumination is a vulnerability for depression and potentially linked to inhibitory control weaknesses. We aimed to replicate the association observed in adults between inhibitory control and rumination in adolescents, and to examine putative moderating roles of childhood maltreatment and perceived family cohesion in an adolescent sample at risk for depression due to familial/personal history. Ninety adolescents aged 11–17 (M = 14.6, SD = 1.8) completed self-report scales of rumination, maltreatment, and family cohesion, and performed a task assessing inhibitory control. Hierarchical regression models showed no significant relation between inhibitory control and moderator variables on rumination. However, adolescents who reported higher levels of maltreatment and who perceived lower family cohesion tended to indicate higher levels of rumination (B = 27.52, 95% CIs [5.63, 49.41], B = -0.40, 95% CIs [-0.65, -0.15]). These findings demonstrate an alternative understanding of factors that increase depression onset risk and recurrence in adolescents. Summary Statement: This study was funded by the National Institute of Mental Health grants R61MH116080 and F31MH117856. S.A.L. reports financial disclosures from EPI-Q, Otsuka Pharmaceutical, Development and Commercialization, Inc, and Secondary Triad, Inc, all of which are unrelated to the present work. S.A.L. is supported by National Institute of Mental Health grants (Grant Nos. MH116080, MH112705, MH120660, and MH120168). K.L.B. is supported by the National Institutes of Mental Health grant F31MH117856. All other authors have no relevant financial or non-financial interests to disclose.